Синтез частиц титана алюминия анизотропной формы при протекании твердофазных реакций в системе гидроксид алюминия–диоксид титана - Шапорев, Валерий Павлович; Шестопалов, Алексей Валерьевич (НТУ "ХПИ", 2014)
У статті наведено дані з процесу утворення нитковидних кристалів титанату алюмінію при протіканні твердофазної реакції в системі гідроксид алюмінія–диоксид титану. Доведено, що при нагріванні утворення нової фази (Al₂TiO₅) зобов'язано низькотемпературним [Т≈(0,1–0,4) Tпл продукту] процесам масопереносу, а зростання кристалів анізотропної форми проходить внаслідок кристалізації утвореної рентгеноаморфної нової фази. Визначено температурні інтервали процесу, розміри кристалів, відношення поперечного розміру кристала до його длини, а також кристалографічна орієнтація. На основі здобутих кристалів вироблені орієнтовано спечені матеріали з індексом Лотжеринга F//a = 0,88.

In the article information is resulted from the process of whiskerization aluminum ti-tanate (ATI, Al₂TiO₅) at flowing firmly phase reaction in the system aluminium hydroxide-titanium dioxide. It is well-proven that at heating of formation of new phase (Al₂TiO₅) due to low temperature [T(0,1–0,4) Tm of product] processes of mass transfer, and growth of crys-tals of anizotrop form passes as a result of crystallization x-ray photography of amorphous new phase. Certain temperature intervals of process, sizes of crystals, relations of transversal size of crystal, to his length, and also orientation of crystallography. On the basis of the ob-tained crystals mined-out sintered materials are oriented with Lotgering factor F//a = 0,88.
Sintasis of phase of anizotrop form aluminum titanate at flowing of firmly phase reaction in the system aluminium hydroxide-titanium dioxide
Keywords: огнеупорные материалы; титанат алюминия; термоудары